Ecology matters: Atlantic–Mediterranean disjunction in the sand‐dune shrub Armeria pungens (Plumbaginaceae) - ROSALÍA PIÑEIRO; JAVIER FUERTES AGUILAR; DAVID DRAPER MUNT; GONZALO NIETO FELINER (Molecular Ecology, 2007)
Inferring the evolutionary history of Mediterranean plant lineages from current genetic, distributional and taxonomic patterns is complex because of a number of palaeoclimatic and geological interconnected factors together with landscape heterogeneity and human influence. Therefore, choosing spatially simplified systems as study groups is a suitable approach. An amplified fragment length polymorphism (AFLP) study using two restriction enzyme combinations ( Eco RI/ Mse I and Kpn I/ Mse I) was carried out to estimate the structure of genetic variation throughout the range of Armeria pungens . This species has a West Iberian‐Corso/Sardinian disjunct distribution on coastal sand‐dune ecosystems. Bayesian, amova and genetic distance analyses of the AFLP data revealed the same distinguishable genetic groups, which do not match the main geographical disjunction. Corso‐Sardinian populations were found to be genetically closer to southwest Portuguese than to those from the Gulf of Cadiz (the closest geographically). Eastwards long‐distance dispersal is therefore invoked to explain this geographical disjunction. A GIS analysis based on bioclimatic envelope modelling aiming to characterize the current locations of A. pungens found strong similarities between the Portugal and Corsica‐Sardinia sites and less so between these areas and the Gulf of Cadiz. This coincident pattern between AFLP and climatic data suggests that the geographical disjunction is better explained by climatic factors than by the likeliness of a stochastic dispersal event. Such a combined phylogeographical–GIS modelling approach proves to be enlightening in reconstructing the evolutionary history of plant species.